The classical obstacle problem with Hölder continuous coefficients. (January 2023) - Andreucci, Giovanna; Focardi, Matteo
Abstract: Weiss' and Monneau's type quasi-monotonicity formulas are established for quadratic energies having matrix of coefficients which are Dini, double-Dini continuous, respectively. Free boundary regularity for the corresponding classical obstacle problems under Hölder continuity assumptions is then deduced.